Winter foraging dynamics of woodland caribou in an artificial landscape - Rominger, Eric M.; Robbins, Charles T. (Rangifer, 1996)
The data suggest that arboreal lichen biomass and/or bite size are primary factors influencing intake rate. Caribou did not increase bite rate to compensate for smaller bite sizes or decreased biomass. Forest management should enhance lichen production to maximize intake rates for woodland caribou.